Menstrual cycle effects on sleep - PD, Gupta (Clinical Journal of Obstetrics and Gynecology, 2022)
Sleep and menstrual cycle both are normal physiological processes in women’s life but they are regulated by different centers. Sleep is a daily rhythm whereas the menstrual cycle lasts for 28 days. During this period the estrogen peaks twice. We have shown earlier that there is an inverse relationship between estrogen and the hormone melatonin which aids sleep. Because of this menstruating women will have sleep disorders.